Papulonecrotic tuberculid with positive acid-fast bacilli - Ren Jun; Liu Xiao-kun; Pan Chao; Li Xin-sheng; Wang Xiao-hui; Yan Xin; Chen Mei-hua; Zeng Kang (Wolters Kluwer Medknow Publications, 2013)
Two patients suffered from 'boils' on their arms and/or thighs for several months. A diagnosis of papulonecrotic tuberculid (PNT) was made based on clinical, laboratory parameters, histopathology, and a prompt response to multi-drug anti-tuberculosis treatment. We checked the pathological sections carefully and finally found a small amount of positive acid-fast bacilli. We analyzed the clinical and histopathological features of PNT in order to offer reference of preventing and controlling the disease.